Ultra-Wideband Signal Generation Based on a Silicon Segmented Mach-Zehnder Modulator - Gangqiang Zhou; Yuyao Guo; Liangjun Lu; Jianping Chen; Linjie Zhou (IEEE Photonics Journal, 2020)
In this paper, we demonstrate a method to generate a low-chirp ultra-wideband pulse (UWB) signal based on a silicon single-drive push-pull segmented Mach-Zehnder modulator (SMZM). The concept is analyzed theoretically and demonstrated experimentally. We get positive monocycle pulses with different relative time delays between the two driving signals. The center frequency and fractional bandwidth of the generated positive monocycle pulse is 5.97 GHz and 161% with a relative time delay of 56 ps. By changing the operating point of the SMZM, we can get negative monocycle pulses. We modulate the UWB signals with on-off keying and pulse position formats by properly coding the driving signal. As far as we know, this is the first time to realize low-chirp UWB signals using only one silicon modulator. The successful generation of UWB signals poses a significant step in realizing a compact low-cost and low-chirp UWB generator on the silicon photonics platform.